Progress in the diagnosis of immunoglobulin G4-related coronary arteritis - Lai-Sheng MIAO; Ru-Ping DAI (Yixue xinzhi zazhi)
The histopathological features of IgG4-related coronary arteritis involve a large number of IgG4-positive plasma cell infiltrates in the tissues of the coronary adventitia, causing adventitia fibrosis and diffuse enlargement, forming a boudoir mass around the coronary artery with neoplastic thickening of the artery wall. CT angiography of the coronary artery shows the thickening of the coronary vessel wall and the mistletoe sign formed by the surrounding tumor-like mass which are the characteristic manifestations of this disease. This article expounds on IgG4-related coronary arteritis and explains its pathogenesis, imaging features and diagnostic criteria.